2020
DOI: 10.1002/anie.202007237
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Single‐Molecule Conductance in Metalloporphyrin‐Based Wires via Supramolecular Interactions

Abstract: Nature hasd eveloped supramolecular constructs to delivero utstanding charge-transport capabilities usingm etalloporphyrin-baseds upramoleculara rrays. Herein we incorporate simple,n aturally inspired supramolecular interactions via theaxial complexation of metalloporphyrinsintothe formation of as ingle-molecule wire in an anoscale gap. Smalls tructural changesi nt he axialc oordinatingl inkers result in dramatic changesi nt he transportp ropertieso ft he metalloporphyrinbasedw ire. Thei ncreased flexibilityo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The three previously reported conductance features I‐III for the [Co II (DPP)]/PyrMT system, [29] are also identified in all four studied metal porphyrins (Co, Ni, Cu, Zn). In all cases, the low conductance features II and III display small variations upon inversion of the Ni tip magnetization direction, within narrow conductance ranges of 0.8–1×10 −2 G o and 2–3×10 −3 G o for II and III, respectively.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The three previously reported conductance features I‐III for the [Co II (DPP)]/PyrMT system, [29] are also identified in all four studied metal porphyrins (Co, Ni, Cu, Zn). In all cases, the low conductance features II and III display small variations upon inversion of the Ni tip magnetization direction, within narrow conductance ranges of 0.8–1×10 −2 G o and 2–3×10 −3 G o for II and III, respectively.…”
Section: Resultssupporting
confidence: 64%
“…In all cases, the low conductance features II and III display small variations upon inversion of the Ni tip magnetization direction, within narrow conductance ranges of 0.8–1×10 −2 G o and 2–3×10 −3 G o for II and III, respectively. These two conductance features have been previously ascribed to junction configurations arising from direct pyridinyl/DPP ring interactions via π–π stacking or/and hydrogen bonding with little or no orbital contribution from the metal center [29] . Likewise, the high conductance feature I has been univocally assigned to the pyridinyl coordination of the metal center [20] and it is observed that its conductance value depends on both the metal center (M II =Co, Ni, Cu and Zn) and the Ni magnetization sign (α, β) (Figure 2).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…More recently, they investigated the effect of different linkers (for electrode coating) on the configurations of supramolecular junctions using the same technique with an applied bias voltage of 7.5 mV. 63 They used pyridine-4-thiol ( PyrT ) and the previously used pyridin-4-ylmethanethiol ( PyrMT ) as electrode coating materials to study junctions after exposition to porphyrin 40 , 5,15-bisphenyl porphyrin 41 , and their Co complexes 42 and 43 , respectively (see Fig. 15(a) ).…”
Section: Single-molecule Porphyrin Junctionsmentioning
confidence: 99%